ONLINE POLYPHONIC CHOIR LESSONS IN PANDEMIC PERIOD - Kaçmaz, Derya; Bayburtlu, Ahmet Selçuk (My University, 2022)
Choir lessons; It creates a very important common ground for students and teachers in terms of learning basic music information, reinforcing vocal education in a community, strengthening the concepts of intonation and musicality, acquiring choral culture and manners, and working together. This research was carried out in order to determine the efficiency of the choir lessons made with online applications, the participation of the students in the lesson, the perception of musical sensation and musicality, and to determine the effects of the pandemic process on the lesson. The research is a descriptive study and as a data collection technique; structured interview questions prepared by researchers through Google Questions ıt was directed to undergraduate music program students (n=254) selected as the sample group. Obtained data were analyzed with SPSS, t test and anova analysis were used as parametric tests. As a result of the research, the majority of the participating students positively evaluated the online choir lessons process.
Keywords: Eğitim; Eğitim Araştırmaları; Sanat